Typification of Bromelia karatas, the type of the genus Bromelia (Bromeliaceae). Issue 5 (27th October 2016) - Monteiro, Raquel F.; Forzza, Rafaela C.
Abstract: The type of the genus Bromelia, B. karatas, occurs in Mexico, the Caribbean, Central and northern South America. Over the last two centuries, the absence of type material has led to uncertainty regarding the identity of this taxon. Here we lectotypify and epitypify B. karatas, the species upon which the type genus of Bromeliaceae is based, and clarify the application of this name.